Răspuns :
a)
[tex]9 \frac{3}{4} + 3 \frac{1}{6} = \\ \frac{9 \times 4 + 3}{4} + \frac{3 \times 6 + 1}{6} = \\ \frac{36 + 3}{4} + \frac{18 + 1}{6} = \\ \frac{39}{4} + \frac{19}{6} = \\ aduc \: la \: acelasi \: numitor \\ amplific \: prima \: fractie \: cu \: 3 \: si \: pe \: a \: doua \: cu \: 2 \\ \frac{117 + 38}{12} = \frac{155}{12} [/tex]
b)
[tex]7 \frac{8}{15} + 8 \frac{17}{20} = \\ \frac{7 \times 15 + 8}{15} + \frac{8 \times 20 + 17}{20} = \\ \frac{100 + 8}{15} + \frac{160 + 17}{20} = \\ \frac{108}{15} + \frac{177}{20} = \\ aduc \: la \: acelasi \: numitor \: amplificand \: prima \: fractie \: cu \: 4 \: si \: pe \: a \: doua \: cu \: 2 \\ \frac{432 + 354}{60} = \frac{786}{60} \\ simplific \: cu \: 2 \\ = \frac{393}{30} \\ simplific \: cu \: 3 \\ = \frac{131}{10} [/tex]
c)
[tex]11 \frac{7}{12} + 6 \frac{11}{18} = \\ \frac{11 \times 12 + 7}{12} + \frac{6 \times 18 + 11}{18} = \\ \frac{139}{12} + \frac{119}{18} = \\ prima \: cu \: 3 \: a \: doua \: cu \: 2 \\ \frac{417 + 238}{36} = \frac{355}{36} [/tex]
d)
[tex]7 \frac{3}{8} + 11 \frac{7}{12} = \\ \frac{7 \times 8 + 3}{8} + \frac{11 \times 12 + 7}{12} = \\ \frac{59}{8} + \frac{139}{12} \\ prima \: cu \: 3 \: a \: doua \: cu \: 2 \\ \frac{177 + 278}{24} = \frac{455}{24} [/tex]
e)
[tex]3 \frac{5}{9} + 1 \frac{7}{12} = \\ \frac{3 \times9 + 5}{9} + \frac{12 \times 1 + 7}{12} = \\ \frac{32}{9} + \frac{19}{12} \\ prima \: cu \: 4 \: a \: doua \: cu \: 3 \\ \frac{128 + 57}{36} = \frac{185}{36} [/tex]
f)
[tex]3 \frac{1}{7} + \frac{4}{5} = \\ \frac{ 7\times 3 + 1}{7} + \frac{4}{5} = \\ \frac{22}{7} + \frac{4}{5} = \\ prima \: cu \: 5 \: a \: doua \: cu \: 7 \\ \frac{110 + 28}{35} = \frac{138}{35} [/tex]
g)
[tex]3 \frac{1}{14} + 2 \frac{4}{21} = \\ \frac{3 \times 14 + 1}{14} + \frac{2 \times 21 + 4}{21} = \\ \frac{43}{14} + \frac{46}{21} = \\ prima \: cu \: 3 \: a \: doua \: cu \: 2 \\ \frac{129 + 92}{42} = \frac{221}{42} [/tex]
[tex]9 \frac{3}{4} + 3 \frac{1}{6} = \\ \frac{9 \times 4 + 3}{4} + \frac{3 \times 6 + 1}{6} = \\ \frac{36 + 3}{4} + \frac{18 + 1}{6} = \\ \frac{39}{4} + \frac{19}{6} = \\ aduc \: la \: acelasi \: numitor \\ amplific \: prima \: fractie \: cu \: 3 \: si \: pe \: a \: doua \: cu \: 2 \\ \frac{117 + 38}{12} = \frac{155}{12} [/tex]
b)
[tex]7 \frac{8}{15} + 8 \frac{17}{20} = \\ \frac{7 \times 15 + 8}{15} + \frac{8 \times 20 + 17}{20} = \\ \frac{100 + 8}{15} + \frac{160 + 17}{20} = \\ \frac{108}{15} + \frac{177}{20} = \\ aduc \: la \: acelasi \: numitor \: amplificand \: prima \: fractie \: cu \: 4 \: si \: pe \: a \: doua \: cu \: 2 \\ \frac{432 + 354}{60} = \frac{786}{60} \\ simplific \: cu \: 2 \\ = \frac{393}{30} \\ simplific \: cu \: 3 \\ = \frac{131}{10} [/tex]
c)
[tex]11 \frac{7}{12} + 6 \frac{11}{18} = \\ \frac{11 \times 12 + 7}{12} + \frac{6 \times 18 + 11}{18} = \\ \frac{139}{12} + \frac{119}{18} = \\ prima \: cu \: 3 \: a \: doua \: cu \: 2 \\ \frac{417 + 238}{36} = \frac{355}{36} [/tex]
d)
[tex]7 \frac{3}{8} + 11 \frac{7}{12} = \\ \frac{7 \times 8 + 3}{8} + \frac{11 \times 12 + 7}{12} = \\ \frac{59}{8} + \frac{139}{12} \\ prima \: cu \: 3 \: a \: doua \: cu \: 2 \\ \frac{177 + 278}{24} = \frac{455}{24} [/tex]
e)
[tex]3 \frac{5}{9} + 1 \frac{7}{12} = \\ \frac{3 \times9 + 5}{9} + \frac{12 \times 1 + 7}{12} = \\ \frac{32}{9} + \frac{19}{12} \\ prima \: cu \: 4 \: a \: doua \: cu \: 3 \\ \frac{128 + 57}{36} = \frac{185}{36} [/tex]
f)
[tex]3 \frac{1}{7} + \frac{4}{5} = \\ \frac{ 7\times 3 + 1}{7} + \frac{4}{5} = \\ \frac{22}{7} + \frac{4}{5} = \\ prima \: cu \: 5 \: a \: doua \: cu \: 7 \\ \frac{110 + 28}{35} = \frac{138}{35} [/tex]
g)
[tex]3 \frac{1}{14} + 2 \frac{4}{21} = \\ \frac{3 \times 14 + 1}{14} + \frac{2 \times 21 + 4}{21} = \\ \frac{43}{14} + \frac{46}{21} = \\ prima \: cu \: 3 \: a \: doua \: cu \: 2 \\ \frac{129 + 92}{42} = \frac{221}{42} [/tex]